THE OPTIC PATHWAYS GLIOMAS IN CHILDREN WITH NEUROFIBROMATOSIS 1 - Ramona Filipescu; Ion Poeata; Ioana Grigore; Georgeta Diaconu (Amaltea Medical Publishing House, 2014)
Optic pathways gliomas have the maximal clinical expression in childhood around the age of 5, being the second tumor in neurofi bromatosis type 1 in frequency.Considering their location,it describes three types of optic pathways gliomas: type I - retrobulbar gliomas, type II - optic tracts gliomas and type III - chiasmatic gliomas. Neuroimaging exams are essential in diagnosis and selection surgical patients. Management of these tumors is often diffi cult even they exhibit histological benign features. Patients harboring optic nerve gliomas with symptomatic and documented neuroimaging progression have indication of tumor resection. Optic nerve gliomas associated with neurofi bromatosis type 1 have generally a good prognosis. Unfavorable prognostic factors are represented by the early clinical onset under 6 years of age and chiasmatic and retrochiasmatic location.